Planeamiento estratégico para mejorar la calidad de servicio de atención al cliente en una Entidad Financiera de Trujillo, 2018 - Méndez Ibáñez, Milka Lourdes (2019)
Currently companies must add value to their products or services in order to differentiate and position themselves in the mind of the consumer, customer service is essential to attract more customers and the Banco de Credito del Peru seeks to improve this aspect that is extremely fundamental to position yourself in the consumers._x000D_ The research was carried out with a total sample of 385 clients who request services from the Bank, applying a quantitative, applied and explanatory methodology; with pre-experimental design. The customer survey was conducted by applying a test to measure the level of customer service before and after strategic planning. Statistical tables and graphs were constructed as well as the hypothesis test t for the sample._x000D_ The scores obtained in the pre-test and post-test (before and after) of the strategic planning are observed, where the differences of the scores is 2.1 points and this difference is significant; the average level of quality of service for each dimension, before strategic planning on average in all dimensions, is an average quality of 3.32. To then have an average level of service quality of 3.52; therefore, it can be concluded that through strategic planning, customer service has improved